Thickness effect on the easy axis distribution in exchange biased Co/IrMn bilayers - Tarazona H.S. (2019)
This work has been partially supported by the Brazilian agencies CNPq and FAPERJ. H. S. T. thanks to the Peruvian Doctoral Scholarship Program of CIENCIACTIVA (CONCYTEC) for financial support under Grand #218-2014-FONDECYT. J. Q-M and C. V. L. are grateful to CIENCIACTIVA (CONCYTEC) for partial financial support through the Excellence Center Programs. J. Q-M is also grateful to the GEMaC Laboratory, for the hospitality during the preparation of this manuscript. In addition, E. B. S. acknowledges support from FAPERJ through several grants including Emeritus Professor fellow and CNPq for BPA and corresponding grants.